ONLINE DISPUTE RESOLUTION SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA TRANSAKSI DIGITAL - Armansyah - (Jurnal Hukum dan Bisnis (Selisik), 2021)
The development of information technology (IT) is an impact of the progress of the globalization era. Several variants of activities in it include trading activities (e-commerce). This sale and purchase transaction via the internet is without any face-to-face contact between the parties, based on mutual trust. This condition, of course, can pose a risk with all the legal consequences, including an act against the law, either civil or criminal from one of the parties in an online buying and selling transaction. Although consumer protection in digital transactions has been regulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) and Government Regulation No. 82 of 2012 concerning Implementation of Electronic Systems and Transactions ( PP PSTE), and Government Regulation Number 80 of 2019 concerning Trading Through Electronic Systems (PMSE). The vulnerability of this transaction leads to problems that harm consumers, so it is necessary to find alternative solutions, not only through SELISIK - VOLUME 7, NOMOR 2, DESEMBER 2021ISSN: 2460-4798 (PRINT) & 2685-6816 (ONLINE)35litigation, but also through mediation through the Online Dispute Resolution (ODR) mechanism. This paper raises legal remedies that can be taken by consumers in the event of a criminal act of fraud by business actors in digital transactions and legal protection for consumer disputes in digital transactions through the ODR mechanism. ODR as a prospective application in the context of legal reform in the field of digital transaction dispute resolution. Second, legal protection for consumer disputes in digital transactions through the ODR mechanism is an alternative online resolution of consumer complaints based on the freedom to choose the law and dispute resolution. 33 The ITE Law, in addition to providing benefits from aspects of time and cost savings, convenience of the ODR procedure, selection of the third parties in digital transaction dispute resolution